Meningkatkan Kemampuan Membaca Dan Kepercayaan Diri Anak Di Panti - Arum Septyaningrum; Mia Aulina (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Reading is an important aspect of life. The interest of each child in reading depends on the motivation that is within him. Lack of reading ability often occurs in children, especially children sho are studying in elementary school. This also happened to several elementary school student at the Al Washliyah Binjai Orphanage. There is one child who fells left behind with his friends, namely F. Lack of motivation and confidence in F makes her not dare to start changes. The next step is to provide assistance by running a mini project that has been planned for 1st PKL which is currently being held. The method used in providing this assistance is the Casework intervention method. This Casework intervention method is carried out in several stage, starting with the engagement, intake, and contract stages. Then proceed with the assessment, planning, intervention, and end with the termination stage.